Efektivitas Formulasi Sterilan terhadap Jenis Eksplan pada Kultur Durian Lahung (Durio dulcis): Effectiveness of Sterilant Formulation on Type of Explant in Durian Lahung Tissue Culture - Nofia Hardarani; Chatimatun Nisa (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2022)
Durian lahung is a type of endemic durian to Kalimantan which has a unique characteristic, namely its red skin. The existence of this plant is almost extinct so that conservation needs to be done and one way is to use tissue culture techniques. As first step, it is necessary to conduct experiments to obtain the right sterilization method in order to obtain aseptic planting material. This study aims to determine the effectiveness of sterilant formulation on type of explant for lahung durian culture. This study was designed using two factors factorial Completely Randomized Design (CRD) and was repeated four times. The first factor was formulation of sterilant which consists of five levels and the second factor was type of explant which consists of two levels, i.e leaf and node. The results showed that the combination of sterilant formulation tween 20, fungicide, bactericide, Bayclin 20%, alcohol 70%, HgCl2 0,05%, H2O2 17,6% with leaf explant produced the highest percentage of browning until 4 wap. There was no browning in all combinations of sterilant formulations with node explant. The sterilant formulation tween 20, fungicide, baktericide, alcohol 70% gave the longest time to appear contamination and browning, smaller percentage of contamination and greater percentage of live explants at 2 and 3 wap, while at 4 wap it was obtained from the sterilant formulation tween 20, fungicide, bactericide, Bayclin 20%, alcohol 70%, HgCl2 0,05%. Leaf explants had lower percentage of contamination and higher percentage of live explants than node explants.